Navarra y las reformas monetarias de Felipe V - Francisco Olmos, José María de (Huarte de San Juan. Geografía e Historia, 2007)
The arrival of the House of Borbón to the throne of Spain supposed the beginning of a deep restructuring of the relationships among the peninsular different territories. After War of Succession the law and the currency of Castile transformed into the law and the currency of Spain (except for in the special case of Navarrese), and after being reformed by Felipe V the Castilian new currency she would stay practically unalterable during almost one century. The new denominations should be those accepted in the mercantile accounting of all the territories, but there were many resistances and it was continued using the traditional system in many places, to what was added that they also stayed the denominations of old bill currencies or already extinguished. Everything marks it the use of dozens of monetary denominations that we try to order in this work, to explain, to locate and mainly to give them a value of change standardizes in front of the rest of systems and mainly in relation to the Castilian new currencies so that we can understand in their entirely any document of the time.
Keywords: Felipe V; monetary peninsular systems; monetary reforms; national silver; provincial silver; exchange systems